2004
DOI: 10.1093/ije/dyh183
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of non-Hodgkin's lymphoma and hepatitis C virus infection in Egypt

Abstract: These data support the hypothesis that NHL is a malignant outcome of chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
3
34
1
Order By: Relevance
“…The number of patients with non‐Hodgkin's lymphoma (NHL) attributed to HCV was based on published data and age‐standardised incidence rates (ASR) of NHL in Egypt 10, 11, 12, 13. The age and gender distribution of NHL was obtained from the Gharbia cancer registry 14.…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients with non‐Hodgkin's lymphoma (NHL) attributed to HCV was based on published data and age‐standardised incidence rates (ASR) of NHL in Egypt 10, 11, 12, 13. The age and gender distribution of NHL was obtained from the Gharbia cancer registry 14.…”
Section: Methodsmentioning
confidence: 99%
“…555 Similarly, other studies have not reported increased NHL risk in association with HCV infection, [555][556][557][558][559][560][561] whereas numerous other studies have reported positive associations. 561,[562][563][564][565][566][567][568][569][570][571][572][573][574][575][576][577][578][579] Gisbert et al 580 conducted a meta-analysis of studies that compared the prevalence of HCV infection in B-cell lymphoma cases with that in controls. An excess risk (meta-OR 5 10.82, 95% CI, 7.34-15.94) of NHL was reported across 10 studies that provided odds ratios.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…Egyptian patients with NHL were 2.3 times more likely to have HCV-RNA in their sera than matched controls. 33 …”
Section: Magnitude Of Hcv-caused Chronic Liver Disease In Egyptmentioning
confidence: 99%